Crude Incidence of Childhood Cancer in Children admitted to the Institude of Nuclear Medicine Moleculer Biology and Oncology (INMO)Wad medani ,Gazira state (1999-2004). - Haroun, Huda; Ali, Amal; Elsheik, Sara (Gezira Journal of Health Sciences; Vol 3 No 2 (2007), 2007)
Over the past 20 years, there has been some increase in the incidence of children diagnosed with all forms of invasive cancer (1) .  During this same period, however, death rates declined dramatically and 5-year survival rates increased for most childhood cancers (2) .  This improvement in survival rates is due to significant advances in treatment, resulting in cure or long term remission for a substantial proportion of children with cancer (3) .  With 90% of the world children living in developing countries, the third world bears the greatest burden of paediatric cancer . Much of the burden of cancer incidence, morbidity and mortality which occur in the developing countries, result from a large epidemiological transition in which the chronic non-communicable disease, once limited to industrialized nations, is now increasing in developing countries. In addition to the accumulating risks associated with diet, tobacco, lack of exercise and industrial exposure, some of these risks are attributed to infectious diseases (3) . These disparities in cancer risk combined with poor access to epidemiological data, research, treatment and cancer control and prevention, have resulted in significantly poor survival rates in developing countries . Sudan is one of the developing countries which bears such burden. The absence of a population based cancer registry in the country, makes the available data only hospital based and the fact that there are only two centres in Sudan, where patients with cancer are treated, makes knowledge about cancer in Sudan, like other African countries, very sparse, because cancers and other non communicable diseases were thought to be unimportant public health problems due to the high prevalence of communicable diseases. Despite the problems associated with interpreting data from hospital based registry,  we are trying to present a picture as close as possible to the true situation Prevailing now. The objective of this study is to determine the incidence of childhood cancer in children admitted to the Institute of Nuclear Medicine, Molecular Biology and Oncology (INMO). Gezira State, Sudan